Inclusive-Multicultural Islamic Education for Former Terrorist Convicts - Nugroho, Muhammad Aji (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
An extreme understanding of terrorists departs from the construction of inaccurate knowledge of the Al-Qur'an and Al-Hadith, thus showing Islam's scary and intolerant face. This fact is a severe note to the world of Islamic education, which is accused of contributing to giving birth to this exclusive understanding. That is contrary to the mission of Islam, which is rahmatan lil alamin. This study aims to describe inclusive-multicultural Islamic education for ex-convicts from the theory, implementation, and implications for deradicalization programs through religious counseling. This research is qualitative research with a phenomenological approach. This approach uses observation and interview methods in digging and exploring data, which is strengthened by triangulation of sources and techniques. The results obtained from the process of implementing inclusive-multicultural Islamic education for ex-convicts: 1) forming a new understanding of previously inappropriate doctrines; 2) forming attitudes and behaviors that are more tolerant, humanist, pluralist, and multicultural in society; 3) able to adapt to the various realities of life without losing their identity; 4) more open in socializing and accepting the existing culture; 5) showing a more peaceful face of religion. It confirms that the formation of an inclusive multicultural understanding of religion has successfully managed the deradicalization program for ex-convicts' views.